If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -9x = 11x + 4 Reorder the terms: 24 + -9x = 4 + 11x Solving 24 + -9x = 4 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 24 + -9x + -11x = 4 + 11x + -11x Combine like terms: -9x + -11x = -20x 24 + -20x = 4 + 11x + -11x Combine like terms: 11x + -11x = 0 24 + -20x = 4 + 0 24 + -20x = 4 Add '-24' to each side of the equation. 24 + -24 + -20x = 4 + -24 Combine like terms: 24 + -24 = 0 0 + -20x = 4 + -24 -20x = 4 + -24 Combine like terms: 4 + -24 = -20 -20x = -20 Divide each side by '-20'. x = 1 Simplifying x = 1
| 7+4x-5x=11 | | 5x+11+4x-17-16x+8x+31=34+-2x | | x^3-15x+3=0 | | x/1.6=13 | | x+6/3=x+134x11 | | -5x+6+x=-22 | | ln(x+3)+ln(x)=ln(x+24) | | 5x+11+4x+-17-16x+8x+31=34+-2x | | 5x+7+x=37 | | 20=40-4j | | 1/x-1+5=26/x-1 | | ln(x+3)-ln(x)=ln(x+24) | | 5-10x=105-38x | | 1/x-1+26/x-1 | | 5c+11+4x-17-16x+8+31=34-2x | | M-12=m/5 | | 23=x+2x+2 | | 13-5x=23 | | 7+x/2=22 | | 50=4x+6x-10 | | (x+44)(3x-2)=0 | | 5(a+3)=2(a-2) | | 15=-3x+2x+6 | | 5+2x-3x=-6 | | 154-3x=24x+22 | | 14-9x=36-23x | | 9-2x-3x=69 | | -x+6-4x=-14 | | 1+x+6x=64 | | .59x=x-338 | | -(8c+4d)/8c-(8c-11d)/8c | | 6x+12=89-5 |